2016
DOI: 10.1017/s1368980016002317
|View full text |Cite
|
Sign up to set email alerts
|

Child-directed and nutrition-focused marketing cues on food packaging: links to nutritional content

Abstract: Objective: We tested whether the presence of both child-targeted and nutritionfocused (i.e. parent-targeted) marketing cues on food packaging was associated with the nutritional content of these products. Design: We conducted a quantitative content analysis of 403 food packages chosen randomly from the supermarket's online portal along with all products (n 312) from the cereal aisle in a supermarket from the Southeastern USA. We examined main and interaction effects for cues on nutritional content (e.g. energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 39 publications
3
22
1
Order By: Relevance
“…There was great variability in the types of cues investigated on children and adults, and the influence of many cues remains unexplored. Informational cues, such as nutrition claims, product claims, captions, and call-to-actions are prevalent on children-targeted food packages [17,19], especially of core foods [88]. And yet, our review hardly identified any studies that investigated the impact of these cues on children's food behaviors.…”
Section: Discussionmentioning
confidence: 98%
“…There was great variability in the types of cues investigated on children and adults, and the influence of many cues remains unexplored. Informational cues, such as nutrition claims, product claims, captions, and call-to-actions are prevalent on children-targeted food packages [17,19], especially of core foods [88]. And yet, our review hardly identified any studies that investigated the impact of these cues on children's food behaviors.…”
Section: Discussionmentioning
confidence: 98%
“…This is in agreement with a study in the USA with 715 foods. Authors found that the increased presence of child-targeted cues was associated with more sugar and less fibre and protein [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few papers address the nutritional differences between foods marketed to children and those not marketed to them [ 22 , 25 , 26 , 27 ]. A study in the USA found that the increased presence of child-targeted cues was associated with more sugar and less fibre and protein [ 27 ]. To our knowledge, to date, no similar publications have been found for the Spanish market.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study in Taiwan found that 72.9% of NAS infant food contained more than 10% calories from sugar; this might be because some infant food such ascereal or pure fruit puree contains natural sugar [ 20 ]. Several studies have also reported that many infant and toddler foods with nutrition claims also contain high sugar content or less healthy than those without claims [ 38 , 39 , 40 ]. In the United States, more than half of children’s food products with health or nutrition claims were found to contain more than 20% calories from sugar [ 38 ].…”
Section: Discussionmentioning
confidence: 99%